Defini????o de requisitos de um projeto de customer relationship management na ??rea hospitalar: a proposi????o de um artefato - Oliveira, Hugo Cavalcante de (2020)
The mapping of stakeholder expectations through the definition of requirements is considered a key point for the success of a project. In this context, the health sector is undergoing a paradigm shift, in which the patient, who is the main client of the hospitals, positions himself as the protagonist of his treatment and begins to demand a different posture from the hospitals. The patient, in addition to demanding quality treatment, also requires a personalized relationship according to his profile. Therefore, it is necessary to know better what are the expectations of patients about hospitals in order to create a relationship bond that will build loyalty. Customer Relationship Management (CRM) is a concept that aims to strengthen the relationship between customers and organizations, seeking to improve services and products aimed at the experience of customers. Thus, this dissertation seeks to answer the following question: What are the requirements of a CRM project in the hospital that contemplate the expectations of patients with a focus on improving their relationship with hospitals? This research used Design Science Research, which is considered a collaborative research method, through the construction of a prescriptive artifact, seeks to solve problems in real contexts in organizations, in addition to ensuring the production of reliable scientific knowledge through its methodological rigor. To answer the research question, a theoretical and practical deepening was carried out with the aim of creating an 'model' type artifact of the 'customer relationship' class of problems containing six requirements for the creation of a hospital CRM project that contemplate patients' expectations about their relationship with hospitals. This empirical work was carried out in a 100% private hospital unit in S??o Paulo managed by the group Associa????o Congrega????o de Santa Catarina, the analysis unit has 310 beds fully focused on serving medium and high standard healthcare clients. As a contribution, it is proposed an artifact with requirements for a CRM project that can be instantiated in the practical environment in order to strengthen the relationship of patients with hospitals.